Topics in harmonic analysis related to the littlewood-paley theory. (am-63). - Elias M. Stein (Annals of Mathematics Studies, 2016)
This work deals with an extension of the classical Littlewood-Paley theory in the context of symmetric diffusion semigroups. In this general setting there are applications to a variety of problems, such as those arising in the study of the expansions coming from second order elliptic operators. A review of background material in Lie groups and martingale theory is included to make the monograph more accessible to the student.